Wind energy potential assessment and techno-economic performance of wind turbines in coastal sites of Buenos Aires province, Argentina. Issue 4 (15th March 2016) - Genchi, Sibila A.; Vitale, Alejandro J.; Piccolo, M. Cintia; Perillo, Gerardo M. E.
ABSTRACT: An assessment of wind energy potential was carried out in five sites (four onshore and one offshore) in South-West (SW) of Buenos Aires province (Argentina). We use high-resolution wind data (2 and 5 min) for the period 2009–2012. The power law was used to estimate the wind speed at 30, 40, and 60 m height from the anemometer position. Turbulence intensity and wind direction were analyzed. Statistical analyses were conducted using two-parameter Weibull distribution. A techno-economic analysis based on a set of commercial wind turbines was performed in those sites. The results derived from this work indicate that the SW of Buenos Aires province represents a promising area for the wind energy extraction, which would encourage the construction of wind farms for electricity generation.